1995
DOI: 10.1002/cyto.990210411
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of full‐size mRNA from ethanol‐fixed cells after cellular immunofluorescence staining and fluorescence‐activated cell sorting (FACS)

Abstract: Preparation of intact, full-size RNA from tissues or cells requires stringent precautions against ubiquitous and rather stable RNases. Fluorescence-activated cell sorting (FACS) usually aims at the isolation of cells according to cell surface markers on living cells, from which RNA can be obtained by standard protocols. The separation of cells according to intracellular immunofluorescence markers, such as intranuclear, intracytoplasmic, or secreted molecules, requires permeation of the cell membrane for the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Diez et al (16) reported isolating RNA after using short ethanol fixation and cell sorting. However, this technique can lead to a time-dependent increase in loss of macromolecules through pores in the cell membrane and to rapid nucleic acid degradation by active or insufficiently inactivated ribonucleases (17). The present data regarding cyclin B1 expression levels demonstrated that this methodology generates confirmatory results.…”
Section: Quality Control Of Isolated Rnasupporting
confidence: 56%
See 1 more Smart Citation
“…Diez et al (16) reported isolating RNA after using short ethanol fixation and cell sorting. However, this technique can lead to a time-dependent increase in loss of macromolecules through pores in the cell membrane and to rapid nucleic acid degradation by active or insufficiently inactivated ribonucleases (17). The present data regarding cyclin B1 expression levels demonstrated that this methodology generates confirmatory results.…”
Section: Quality Control Of Isolated Rnasupporting
confidence: 56%
“…Cell fixation, required for specific identification of populations to be sorted, may result in RNA degradation (16). In fact, routinely used fixatives such as ethanol and formaldehyde do not completely inactivate RNAses (17). In the present report, we described a new approach to separate cell cycle populations by fluorescence-activated cell sorter from live cells without cell fixation, followed by isolation of full-length mRNA from sorted cells.…”
Section: Resultsmentioning
confidence: 92%
“…Thus, sorting from organ material based on intracellular markers would in many cases be an attractive option. Unfortunately, the fixation and permeabilization required for intracellular staining can be associated with RNA degradation (1)(2)(3).…”
mentioning
confidence: 99%
“…Reflecting the technical difficulties, only few studies have described molecular analysis of cells flow-sorted for intracellular protein markers (1)(2)(3). Most work has been done on cell lines (1,2), with only one study describing flow sorting from dissociated biopsy specimens (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation